Developing Students' Learning Interest using Math Trail-based Mathematical Modeling with Augmented Reality - Muhammad Ghozian Kafi Ahsan; Adi Nur Cahyono; Iqbal Kharisudin (International Conference on Science, Education, and Technology, 2022)
Abstrak. Learning is currently transitioning to digital learning. This encourages teachers to create a learning environment that can support students’ learning. The results of PISA 2018 show that students' mathematics learning in Indonesia is not good. This is partly due to the low interest in learning mathematics. Therefore, efforts are needed to increase students' interest in learning mathematics. One of them uses mathematical modeling learning. The purpose of this study was to analyze how the influence of learning mathematical modeling on students' interest in learning. This study used a design research approach focused on the retrospective analysis stage with quantitative and qualitative analysis. The results showed that learning mathematical modeling had a positive effect on students' interest in learning. In addition, students' interest in learning can also be shown when learning takes place. Students participate actively during learning activities, ask questions when needed help, and collaborate with each other. It is hoped that with this research, teachers can use the mathematical modeling learning environment as a learning reference.